The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2004
DOI: 10.1103/physrevb.69.125342
|View full text |Cite
|
Sign up to set email alerts
|

Coherent control of tunneling in a quantum dot molecule

Abstract: We demonstrate theoretically that it is possible to use Rabi oscillations to coherently control the electron tunneling in an asymmetric double quantum dot system, a quantum dot molecule. By applying an optical pump pulse we can excite an electron in one of the dots, which can in turn tunnel to the second dot, as controlled by an external voltage. Varying the intensity of the pulse one can suppress or enhance the tunneling between the dots for given level resonance conditions. This approach allows substantial f… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
173
1
5

Year Published

2006
2006
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 246 publications
(183 citation statements)
references
References 22 publications
(28 reference statements)
4
173
1
5
Order By: Relevance
“…Another experimental possibility of choosing a control parameter would be the frequency mismatch between the injected field and the |0 →|1 transition, δ, while ω 12 is kept fixed. However, as detailed in [17], a better electron transfer between the levels is obtained when the levels are off-resonance, thus making the idea of a fixed ω 12 with a varying input pulse frequency less effective for observing clear results in practice. The linear stability of the homogeneous stationary solution is analyzed by studying the response of the system to small fluctuations around the steady state.…”
Section: The Modelmentioning
confidence: 99%
See 2 more Smart Citations
“…Another experimental possibility of choosing a control parameter would be the frequency mismatch between the injected field and the |0 →|1 transition, δ, while ω 12 is kept fixed. However, as detailed in [17], a better electron transfer between the levels is obtained when the levels are off-resonance, thus making the idea of a fixed ω 12 with a varying input pulse frequency less effective for observing clear results in practice. The linear stability of the homogeneous stationary solution is analyzed by studying the response of the system to small fluctuations around the steady state.…”
Section: The Modelmentioning
confidence: 99%
“…2(a), where vanishing absorption is identified at δ = 0.37. Details of such calculations for a variety of QDMs can be found in [17][18][19].…”
Section: The Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…The short time scale of the effect indicates the influence of the higher excitonic states. In a simple approach it has been shown that the damping of the oscillations as the intensity of the short pulse is increased, is due to the off-resonant leakage into biexcitonic levels [28,29]. Taking Ref.…”
Section: Leakage Effectsmentioning
confidence: 99%
“…Up to now, such system has been studied extensively. Under the influence of an external oscillatory (optical pulse or voltage) driving field, one electron can be excited from the valence to the conduction band in one dot, which can in turn tunnel to the second dot [2] [3]. Recent progress in semiconductor nanotechnology indicate that these features have advantages for the application in many quantum devices, such as QD lasers [4][5], QD diodes [6] as well as quantum computing processes [7][8].…”
mentioning
confidence: 99%